1999
DOI: 10.1016/s0006-3495(99)77179-1
|View full text |Cite
|
Sign up to set email alerts
|

Direct Effects of Phosphorylation on the Preferred Backbone Conformation of Peptides: A Nuclear Magnetic Resonance Study

Abstract: Control of protein activity by phosphorylation appears to work principally by inducing conformational change, but the mechanisms so far reported are dependent on the structural context in which phosphorylation occurs. As the activity of many small peptides is also regulated by phosphorylation, we decided to investigate possible direct consequences of this on the preferred backbone conformation. We have performed 1H nuclear magnetic resonance (NMR) experiments with short model peptides of the pattern Gly-Ser-Xa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
66
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 37 publications
14
66
0
Order By: Relevance
“…3c). Previously, it was shown that, unlike serine and threonine phosphorylations, tyrosine phosphorylation had no direct effect on the backbone conformation of model peptides (20). Therefore, the current observation implies that tyrosine phosphorylations of ephrinB2 301-322 , regardless of their locations in the hairpin (Fig.…”
Section: Structural Effects Of Tyrosine Phosphorylationssupporting
confidence: 49%
“…3c). Previously, it was shown that, unlike serine and threonine phosphorylations, tyrosine phosphorylation had no direct effect on the backbone conformation of model peptides (20). Therefore, the current observation implies that tyrosine phosphorylations of ephrinB2 301-322 , regardless of their locations in the hairpin (Fig.…”
Section: Structural Effects Of Tyrosine Phosphorylationssupporting
confidence: 49%
“…The microtubule-polymerization inhibition and tubulin binding activities, the secondary structure content, and the thermal stability of the quadruple mutant 4A were indistinguishable from the wild-type, justifying the validity of the approach (Table 1). To produce the mutant molecules, two silent nucleotide mutations, G66C and G141C, were introduced by PCR into the human pET-16b (Novagen) stathmin clone (7) generating SacI and XhoI recognition sites between the codons for Ser 16 and Ser 25 and Ser 38 and Ser 63 , respectively. This new plasmid provided the basis for subsequent cloning of all mutants by using synthetic oligonucleotide adapter primers at either NdeI/SacI, SacI/XhoI, or XhoI/ BbvCI recognition sites.…”
Section: Methodsmentioning
confidence: 99%
“…ND, not determined. 38 . The isothermal titration calorimetry data of p16,25,38,63 could not be evaluated because binding was too weak.…”
Section: Table 1 Thermodynamic Binding Parameters Derived From the Timentioning
confidence: 99%
See 1 more Smart Citation
“…The most active mutant, NP13D, is also the most unstable (Tm  55.2°C, H  17.9 kcal/mol). Taking into account that at neutral pH aspartic acid has one negative charge, while a phosphoryl group would display an average negative charge of -1.5 [81], 13 Asp would be a reasonable approximation of 7-10 phosphates per monomer in egg NP; however, the fact that this mutant is less stable than egg NP reflects that the conformational properties of phosphorylated NP may not be exactly reproduced [9]. The mutations-induced destabilization of NP is also readily observed by chemical unfolding experiments [9].…”
Section: Effect Of Np Activation Interplay Between Function and Stabmentioning
confidence: 99%